“High specificity of PCR in diagnosing mucocutaneous leshminiasis: a systematic review and meta analysis” - Mohammed Saleh Al-Dhubaibi; Saleh Salem Bahaj; Aref Noman; Waleed Yahya Alkasser; Ahmed Ibrahim AbdElneam; Ghada Farouk Mohammed; Hassan Nawaz; Zeeshan Allana; Sarosh Sher Ali (BMC Infectious Diseases)
Abstract Background Mucocutaneous leishmaniasis (MCL) is a severe form of leishmaniasis causing chronic and destructive lesions. Accurate diagnosis is crucial for effective treatment. Traditional methods, such as the Montenegro skin test is delayed hypersensitivity test. Polymerase chain reaction (PCR) has emerged as a superior diagnostic tool for detecting Leishmania DNA, offering higher sensitivity and specificity. Methodology This meta-analysis adhered to PRISMA guidelines and included studies focusing exclusively on the diagnostic accuracy of PCR for MCL. A comprehensive literature search was conducted across multiple databases. Inclusion criteria mandated studies with relevant diagnostic accuracy metrics, while those mixing other forms of leishmaniasis or lacking a control group were excluded. Quality was assessed using the STARD checklist, and ensuring a low risk of bias assessed through QUADAS-2 tool. Results Eight studies were included, showing PCR sensitivity ranging from 50% to 97.1% and consistently high specificity, often reaching 100%. The studies demonstrated a low risk of bias and applicability concerns, supporting the robustness of the findings. Heterogeneity was substantial, necessitating a random-effects model for pooled estimates. Interpretations This analysis confirms PCR's high specificity for MCL diagnosis, despite variable sensitivity. Compared to previous meta-analyses, this study's focus on MCL exclusively provides a more targeted evaluation. Future research should aim to standardize PCR protocols and explore non-invasive sampling techniques to enhance diagnostic accuracy and patient comfort, ultimately improving clinical outcomes for MCL patients.